PENGARUH KUALITAS PELAYANAN TRANSPORTASI UMUMBUS TRANS JOGJA TERHADAP KEPUASAN KONSUMEN - Arif Wibowo (JURNAL ILMU MANAJEMEN, 2014)
This research  was conducted to examine the effect of Level of Service Quality Public Transport Bus Trans Jogja to customer satisfaction. Trans Jogja bus this is an attempt Yogyakarta Provincial Government since 2008 with the aim to improve public services, especially in the land transport sector in urban areas based DIY to replace the deposit system into a system service purchase. A very important factor in consumer satisfaction is service quality, which is measured in the quality aspects of the service will be a service is satisfied  or not satisfied user when using these services so that these aspects can be seen whether the quality of services provided is good or not good. The quality of transport good services and should attention wants and needs of consumers. Every customer have a perspective different to all forms of transportation layananpada. Whether or not consumers are satisfied with the product will affect the service behavior shown next. The sample used in this study is 100 respondents. The sampling method using purposive sampling. The result show that by using regression (R square)  methods, it can be concluded that tangible of variable positive and significant impact on consumer satisfaction with a significance value (P Value) of 0.308 0.05. While the reliability of a positive and significant effect on customer satisfaction with a significance value (P Value) of 0.305 0.05. Assurance significant positive effect on customer satisfaction with a significance value (P Value) of 0.194 0.05. Responsiveness positive and significant impact on consumer satisfaction with a significance value (P Value) of 0.301 0.05. For empathy and a significant positive effect on consumer satisfaction with a significance value (P Value) of 0.259 0.05.